Pengaruh Disiplin Kerja terhadap Kinerja Aparatur Sipil Negara Pada Kantor Kementerian Agama Kota Jambi - Indra Irawan (Science of Management and Students Research Journal (SMS), 2020)
The purpose of the above study entitled The Effect of Work Discipline on the Performance of the State Civil Apparatus in which the sample of the study was the State Civil Apparatus at the Office of the Ministry of Religion of Jambi, amounting to 89 people is to describe the discipline and Performance of the State civil apparatus at the Office of the Ministry of Religion of the City of Jambi, and to analyze the effect of discipline on the performance of the State Civil Apparatus at the Office of the Ministry of Religion of the City of Jambi. The data analysis technique used is simple linear regression analysis using the SPSS (Statistical Package For Social Science) program. This research is a quantitative descriptive study to find out the factors that influence the performance of the state civil apparatus. Based on the results of regression analysis obtained a simple linear regression equation Y = 22,274 + 0.159 + e, with R square 0.109 meaning that the disciplinary variable influences performance by 10.9% while 89.1% is influenced by other variables not examined in this study. Discipline of the State civil apparatus at the Ministry of Religious Affairs office in Jambi City is very high with an average score of 406.55 and similar to the performance of the State civil apparatus Very high, with an average score of 427.16. Partially, the discipline of the State Civil Apparatus at the Office of the Ministry of Religion of Jambi influences the performance of tcount of 3.261> ttable 1.987 with a significant level of 0.05. then Ho's decision was rejected Hi accepted, there is an influence between discipline on the performance of the State civil apparatus at the Office of the Ministry of Religion of the City of Jambi.